Development of e-Pocket Musafir (e-PM) an Android Mobile App for Muslim Travelers: Pembangunan e-Pocket Musafir (e-PM) Aplikasi Mudah Alih Android untuk Pengembara Muslim - Mohamed Ali, Mohd Hatta; Abdul Samad, Sam Faheeda; Mohamed, Juliana; A. Talip, Bakhreza; Kassim, Noordiana; Abdul Hamid, Mariam (Journal of Quranic Sciences and Research, 2022)
Musafir (?????) is a word in Arabic meaning ‘traveler’ which refers to a person who is on a long journey. According to Quran Verse 6:11 “Say (unto them, O Muhammad): Travel through the earth, and see what was the end of those who rejected it.”. This verse encourages Muslims to travel while observing what is the end for the people who lie to Allah SWT. Even if a person is on a journey, in Islam prayer is obligatory and a person must perform religious obligation. Therefore, Allah SWT has given privileges to Muslims while traveling to perform prayers. Since this way of praying is rarely performed, people who travel must have a reference before performing this prayer, and most references nowadays are in the form of non-interactive documents and are difficult to carry anywhere. Therefore, this project aims to develop a mobile application for Muslim travelers which will guide them to perform prayers with privilege. We are using the incremental model methodology to develop this project. In addition, the application will also provide several important features for Muslims to use such as tasbih, Qasar, and Jamaq prayer guidance, Hadith, and prayer times. A selected group of people a chosen to confirm the project's usability. At the end of the research, we found that this project is successfully helping Muslim travelers to perform prayers whether it is in Qasar or Jamaq prayer states. In conclusion, the effectiveness of this application is likely to be extended into the study of other topic areas.